Pathophysiologic and prognostic importance of cardiac power output reserve in heart failure with preserved ejection fraction - Takizawa, Daiki; Harada, Tomonari; Obokata, Masaru; Kagami, Kazuki; Sorimachi, Hidemi; Yuasa, Naoki; Saito, Yuki; Murakami, Fumitaka; Naito, Ayami; Kato, Toshimitsu; Wada, Naoki; Ishii, Hideki (European heart journal cardiovascular imaging, 2024)
Heart failure with preserved ejection fraction (HFpEF) is a syndrome characterized by multiple cardiac reserve limitations during exercise. Cardiac power output (CPO) is an index of global cardiac performance and can be estimated non-invasively by echocardiography. We hypothesized that CPO reserve during exercise would be associated with impaired cardiovascular reserve, exercise intolerance, and adverse outcomes in HFpEF. Exercise stress echocardiography was performed in 425 dyspnoeic patients [217 HFpEF and 208 non-heart failure (HF) controls] to estimate CPO at rest and during exercise. We classified patients with HFpEF based on the median value of changes in CPO from rest to peak exercise (ΔCPO >0.49 W/100 g). Patients with HFpEF and a lower CPO reserve had poorer biventricular systolic function, impaired chronotropic response during exercise, and worse aerobic capacity than controls and those with a higher CPO reserve. During a median follow-up of 358 days, a composite outcome of all-cause mortality or HF events occurred in 30 patients. Patients with a lower CPO reserve had four-fold and nearly 10-fold increased risks of the outcomes compared with those with a higher CPO reserve and controls, respectively [hazard ratio (HR) 4.05, 95% confidence interval (CI) 1.16-10.1, P = 0.003 and HR 9.61, 95% CI 3.58-25.8, P < 0.0001]. We further found that a lower CPO reserve had an incremental prognostic value over the H2FPEF score and exercise duration. In contrast, resting CPO did not predict clinical outcomes in patients with HFpEF. A lower CPO reserve was associated with biventricular systolic dysfunction, chronotropic incompetence, exercise intolerance, and adverse outcomes in patients with HFpEF.